Requirements for Applying The STEM Approach in Teaching Mathematics from The Point of View of Public School Teachers in Ajloun Governorate - Almomani, Ibrahim Mohamd Yousef (Journal of Educational and Psychological Sciences, 2022)
This Study aimed to identify the requirements for applying the STEM approach in teaching Mathematics from the point of view of public school teachers in Ajloun Governorate, the researcher used the Descriptive approaches, study Sample consisted from (650) Female and male mathematics teacher, chosen randomly, to collect data Questioner used, which consisted (33) paragraph divided to three sector, the result of SPSS analysis shown that the degree of the requirements for applying the STEM approach in teaching Mathematics from the point of view of public school teachers in Ajloun Governorate was moderated with average (3.60 out of 5) , the requirements related to the teacher got the highest average (3.70) with a grade of (high), then the requirements related to the educational content with an average of (3.57) and finally the requirements related to the educational environment with an average of (3.54) and both rated (medium) The finding also showed there is no statistically significant differences at (α≤0.05) refers to teacher sex (male and female) in addition there were statistically significant differences refers to teacher qualification in favor of (High educating). Based on the results, the researcher presented a number of recommendations and proposals to provide the necessary requirements and conduct complementary studies on the subject.